The Power of Proof of Child Witnesses in Criminal Procedure - Suisno; Royani, Achmad; Airlangga, Ganda Adam (Universitas Islam Lamongan, 2025)
Criminal offense cases nowadays not only involve adults, but also involve minors whether it is as a victim, witness, or perpetrator. In its strength of proof, the minor child witnesses do not have strong proof strength because of their labile attitude and thinking. The large number of crime cases involving children and in a court judgment to be discussed in this study shows that only one witness saw, and heard directly a crime, where the witness was still classified as a child and was the consideration of the assembly per team of judges in deciding. The first issue, how is the power of a child witness under the provisions of the statute. The research method adopted in this study is normative jurisprudence with Statute Approach (Statue Approach), collection materials of legal materials using Library Studies. The legal regulations governing child witnesses are Article 171 Paragraph (1), Article 185 Paragraph (7), Article 161 Paragraph (2) of the Code of Criminal Procedure, and Article 1 Number (5) of Law No. Criminal Event Law Act statements given by a child witness although by other witnesses are not considered to be valid evidentiary instruments shall however be admissible as clues and additional other valid instruments of evidence.